A descriptive study defining perceptions of selected Filipino respondents on the concepts of a motel in the Philippines - De Guzman, Frances K.; Mayo, Adelaida Villaraza (2010.)
ABSTRACT Motels may have different connotations based on where they are and how they are introduced in the market. This study sought to determine how selected Filipino respondents perceive the primary functions of a motel in the Philippines and clarify whether the respondents' perceptions on the concept on motels in the Philippines are aligned with the traditional function of a lodging facility.
This is a descriptive study defining perceptions of selected Filipino respondents on the concept of a motel in the Philippines. In order to determine how the respondents perceive the primary functions of motels in the Philippines, the researcher conducted group discussions, surveys, and photo criticisms. Purposive sampling was used in the study.
A total of one hundred twelve (112) respondents were subjected in the survey, and 16 of them were immersed in the group discussions. Five photographs representing the six (6) selected motels - three (3) of which are from the Philippines and the other three (3) are outside the country - were gathered for the photo criticisms.
The results of the study suggest that the concept of motels in the Philippines as perceived by the respondents is inclined towards its "sex-related" functions, which is not aligned with that of its traditional concept. Using Sullivan's principle of "form follows function," the perception was explained to have occurred due to the motels' spatial design and branding.
The relationship of how spaces are designed and branded creates an effect on how the public perceive their functions. However, the findings of the study also indicate that there are already attempts to change the image of local motels as reflected in the interior design of some motel rooms which project wholesome family-friendly spaces. This study encourages designers to widen their perspective in the field of design and realize how the form and the design of spaces affect people's perception regarding their function.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Motels -- Philippines